Novel air duct designs to estimate the windshield demisting issue for a commercial vehicle - Akgunlu, Safak; Ozcan, Onur; Bacak, Aykut; Gonul, Alisan; Taner, Tolga; Dalkilic, Ahmet Selim (SAGE PUBLICATIONS LTD, 2024)
This study is about the fog on the windshields of passenger buses because it makes it hard for drivers to see, which is dangerous. The goal of the research is to come up with an effective way to spread the produced mist. According to the study, the air duct design, which is connected to the car's defroster and defrosting system by Kraft hoses, has to be upgraded. The analysis identifies areas in which the current air duct design might be enhanced and then makes design modifications to create a superior design. By conducting climatic chamber experiments on a vehicle equipped with the first air duct design and tracking the actual air velocity values at the nozzle tips, the success of the new technique is assessed. The boundary conditions for the analysis are the observed values. The study involves the utilization of a commercially available software package to conduct investigations on both the original and modified air duct designs. The software package employs a k-epsilon turbulence model that is known to produce reliable results. The data demonstrate that the adjustments made in light of the comparison produced beneficial effects. The maximum air velocities were increased by 23%, while the pressure loss values of the left and right fans were reduced by 2.5% and 2.9%, respectively, due to the modification of the air duct. Significant energy was saved because of the decrease in fan pressure loss, which led to decreases in the power consumption of the left and right fans of 4.2% and 4.7%, respectively. This comparison shows that the newly built air ducts actually increased the flow rate at the system's fan outlets by 40%.
Keywords: CFD; defogging process; defroster; passenger bus; windshield; OPTIMIZATION; Engineering; Transportation